The Effect of Word Tree Games on Early Childhood Receptive Language Development - Febrianti, Novita Ayu; Zahro, Ianatuz; Siswono, Hendrik (Teaching, Learning, and Development, 2025)
Receptive language in early childhood refers to the child's capacity to hear, understand, and focus on information or to know what a word means. However, many children still struggle with poorly developed receptive language skills. This study aims to ascertain how word tree play affects the development of early childhood receptive language. The word tree game serves as the medium. This study used a pre-experimental experimental method with a pretest-posttest design of one group without the presence of a control class. The subjects of the study were as many as 20 kindergarten children in Group A (aged 4-5 years). This study uses Purposive Sampling because there is only one class. "The word tree media passed the Pretest, Treatment, Posttest, Normality Test, Homogeneity Test, and Hypothesis Test in this study. A sig value of <0.001 indicates that the final result is below the significance threshold of 0.05". Ho was rejected, while Ha was accepted. With this, it can be concluded that the game of Word Tree affects the development of early childhood receptive language.